2022
DOI: 10.1021/acsami.2c15362
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Empowered Holographic Metasurface with Simultaneously Customized Phase and Amplitude

Abstract: Metasurfaces with simultaneously and independently controllable amplitude and phase have provided a higher degree of freedom in manipulating electromagnetic (EM) waves. Compared with phase- or amplitude-only modulation, the capability of simultaneously controlling the phase and amplitude of EM waves can enable holography with a higher resolution. However, this drastically increases the design complexity of holographic metasurfaces, and the design process is usually quite time-consuming. In this paper, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…It was revealed that TCDs-CaO 2 -ZE had excellent biocompatibility and anti-inflammatory effects as well as enhanced wound healing properties in diabetic rats without any cytotoxicity. 71 In another study, Qu et al 72 designed sprayable positively charged CDs for promoting infected wound healing. These CDs were synthesized from p -phenylenediamine and polyethyleneimine by a facile one-pot solvothermal method.…”
Section: Cds and Te-rm Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was revealed that TCDs-CaO 2 -ZE had excellent biocompatibility and anti-inflammatory effects as well as enhanced wound healing properties in diabetic rats without any cytotoxicity. 71 In another study, Qu et al 72 designed sprayable positively charged CDs for promoting infected wound healing. These CDs were synthesized from p -phenylenediamine and polyethyleneimine by a facile one-pot solvothermal method.…”
Section: Cds and Te-rm Applicationsmentioning
confidence: 99%
“…Its sprayable forms were also used to treat a skin infection in mouse model, and the results were promising in promoting would healing without causing any noticeable side effects. 72…”
Section: Cds and Te-rm Applicationsmentioning
confidence: 99%
“…[23] Due to its initial data-driven methodology, deep learning has become a powerful driving force in the context of metasurface design from forward design to inverse design. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Taking the inverse design of the metasurface for instance, the deep neural networks can unfold abstract information automatically from a considerably large amount of data pairs of geometrical structures and corresponding spectral response. [35] Compared with conventional physical-and rule-based methods, deep-learning-assisted metasurface design gets rid of repeated manual labor and timeconsuming simulations and reduces the reliance on specialist experience.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots are a new member of the carbon nanomaterial family, first reported by Xu et al 25 in 2004 and have soon aroused the interest of researchers in various fields. [26][27][28] Compared to traditional semiconductor quantum dots, CDs have superior optical properties, 29,30 good water solubility, [31][32][33] easyto-modify surface [34][35][36] and good dispersion. [37][38][39] Due to these advantages, CDs are increasingly being utilized as fluorescent probes.…”
Section: Introductionmentioning
confidence: 99%